2023
DOI: 10.1186/s12903-023-02989-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a new abutment design concept on the biomechanics of peri-implant bone, implant components, and microgap formation: a finite element analysis

Abstract: Background A new two-piece abutment design consisting of an upper prosthetic component and tissue-level base has been introduced; however, the biomechanical behavior of such a design has not been documented. This study aimed to investigate the effect of a two-piece abutment design on the stress in the implant components and surrounding bone, as well as its influence on microgap formation. Methods To simulate the implant models in the mandibular lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…When assessing the stresses in the abutments the lowest stresses were observed in the tissue level with type IV bone group (115.02 MPa), while the highest were observed in the two-piece with type IV bone group (607.63 MPa). Similar to the analysis by Nie et al., 20 this present study also investigated the von Mises stress values found in different abutments as a result of loading and stress distributions. The implant with a non-hexagonal abutment located in the site of maxillary left canine on model 3 reported the highest von mises value (123.07 MPa) while the lowest stress value (73.50 MPa) was seen on the implant with a hexagonal abutment in place of the maxillary right canine in model 1.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…When assessing the stresses in the abutments the lowest stresses were observed in the tissue level with type IV bone group (115.02 MPa), while the highest were observed in the two-piece with type IV bone group (607.63 MPa). Similar to the analysis by Nie et al., 20 this present study also investigated the von Mises stress values found in different abutments as a result of loading and stress distributions. The implant with a non-hexagonal abutment located in the site of maxillary left canine on model 3 reported the highest von mises value (123.07 MPa) while the lowest stress value (73.50 MPa) was seen on the implant with a hexagonal abutment in place of the maxillary right canine in model 1.…”
Section: Discussionmentioning
confidence: 58%
“…A previous study by Nie et al., 20 completed a similar assessment as the present study by evaluating implant abutment design (internal bone level, tissue level, and a two piece design) and microgap formation on the stress distribution on both the implant and the surrounding bone, including different bone qualities (type II, III, and IV). This previous study reported that the two-piece design with type II bone displayed minimum stress (356.55 MPa) in the implants, whereas the maximum stress occurred in the bone level design with type IV bone (578.29 MPa).…”
Section: Discussionmentioning
confidence: 95%
“…Hence, additional investigation is warranted to address this concern and ensure the sustainability of the procedure. Nie et al 42 suggested in a recent finite element analysis that in standard dental implants (with a 4.3 mm diameter), the distributions of maximum and minimum principal stresses in the peri-implant bone were similar between the connections of the two-piece abutment model and the traditional abutment model.…”
Section: Discussionmentioning
confidence: 98%
“…Many authors consider that, although time-consuming, FEA analysis helps us to explain the occurrence of a series of unwanted phenomena at the level of some teeth, implants, direct or indirect restorations, and the dental materials used, and can indicate the vulnerable areas where maximum stresses and deformations are developed [57][58][59][60][61][62]. Jakupović A. et al [63] found that the type of tooth loading has the greatest influence on the intensity of stress.…”
Section: Discussionmentioning
confidence: 99%